2018
DOI: 10.3390/ijerph15122695
|View full text |Cite
|
Sign up to set email alerts
|

Personal Network Analysis in the Study of Social Support: The Case of Chronic Pain

Abstract: In the context of chronic illness, the individual’s social and relational environment plays a critical role as it can provide the informal support and care over time, beyond healthcare and social welfare institutions. Social Network Analysis represents an appropriate theoretical and methodological approach to study and understand social support since it provides measures of personal network structure, composition and functional content. The aim of this mixed method study is to present the usefulness of Persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 65 publications
2
20
0
1
Order By: Relevance
“…11 A qualitative study indicated that people who experienced pain reported weakened social ties and a tendency towards social isolation compared with the situation before they had pain. 12 Based upon these previous findings, we hypothesize that experiencing pain may contribute to a feeling of low social support. Moreover, it has been proved that low PSS is significantly correlated to higher levels of depression.…”
Section: Mediation Effectmentioning
confidence: 86%
See 1 more Smart Citation
“…11 A qualitative study indicated that people who experienced pain reported weakened social ties and a tendency towards social isolation compared with the situation before they had pain. 12 Based upon these previous findings, we hypothesize that experiencing pain may contribute to a feeling of low social support. Moreover, it has been proved that low PSS is significantly correlated to higher levels of depression.…”
Section: Mediation Effectmentioning
confidence: 86%
“…Therefore, we hypothesize that SRH may mediate the relationship between pain and depression. In addition, pain was shown to have a negative role on PSS, 12 PSS was in turn found to have a negative impact on SRH. 17 With these findings in mind, we also hypothesize that pain is sequentially associated with low PSS first and then poor SRH, which is in turn related to depression.…”
Section: Mediation Effectmentioning
confidence: 97%
“…This research is part of a larger study aimed at examining social support and quality of life in the context of chronic pain [41]. In a prior publication, the descriptive results of this larger study were presented using a mixed approach [42], showing that different types of personal networks were associated with self-reported quality of life, which scored below the populational mean in all dimensions considered.…”
Section: Methodsmentioning
confidence: 99%
“…The data collection included participant variables (ego), their contacts (alter) and details regarding their personal network (see [41,42] for further information regarding the variables): mean of the alter-alter matrix and at node level), betweenness centrality (two measures; mean of a personal network and at node level), number of components and number of isolates.…”
Section: Variablesmentioning
confidence: 99%
“…Social support can relieve individual psychological pressure and eliminate individual psychological barriers and plays an important role in promoting individual mental health [101]. erefore, it is widely used in the study of happiness and physical and mental health.…”
Section: Complexitymentioning
confidence: 99%